Indenting polymer brushes of varying grafting density in a viscous fluid: A gradient approach to understanding fluid confinement. (15th April 2019) - Mathis, Christian H.; Simič, Rok; Kang, Chengjun; Ramakrishna, Shivaprakash N.; Isa, Lucio; Spencer, Nicholas D.
Abstract: A sound understanding of the fluid-confinement mechanics of soft materials, including polymer brushes or hydrogels, is essential for developing advanced biomedical and engineering applications such as contact lenses or low-friction coatings. In order to elucidate the effect of polymer-chain density on fluid confinement in thin films, gradients of poly(dodecyl methacrylate) (P12MA) brushes with varying grafting densities were created via a UV-cleaving process and studied using colloidal-probe atomic force microscopy (CP-AFM) nanoindentation. A recently developed indentation methodology that accounts for viscous squeeze-out effects upon approach allowed for the accurate determination of the properties of the soft, thin materials. The indentation of different grafting densities of brushes of identical molecular weights solvated by a common viscous liquid (i.e. hexadecane) allowed direct comparison of rate-dependent fluid confinement within thin surface-grafted polymer layers. This revealed comparable mechanical properties upon quasi-static indentation for the different grafting-density polymer brushes, showing an elastic modulus of about 0.3 kPa in the topmost part of all layers. At non-finite rates of indentation, the higher grafting densities showed more fluid confinement. The insight gained opens new possibilities for soft thin-layer characterization and provides an accessible technical approach to studying fluid confinement. Graphical abstract: Image 1 Highlights: Poly(dodecylmethacrylate) brushes with varying grafting densities were created via UV cleaving. A recently developed colloidal-probe nanoindentation approach was used to study fluid confinement. Contact modulus below 1 kPa was measured for all grafting densities in hexadecane. Liquid squeeze-out ahead of contact appears to be independent of grafting density. Higher grafting densities showed more fluid confinement within the polymer layer.